2009
DOI: 10.3399/bjgp09x454106
|View full text |Cite
|
Sign up to set email alerts
|

‘A coal face option’: GPs' perspectives on the rise in antidepressant prescribing

Abstract: ParticipantsGPs in 30 practices (n = 63) purposively selected to reflect a range of practice characteristics and levels of antidepressant prescribing. MethodInterviews with GPs were taped and transcribed. Analysis followed a Framework Approach. ResultsGPs offered a range of explanations for the rise in antidepressant prescribing in Scotland. Few doctors thought that the incidence of depression had increased, and many questioned the appropriateness of current levels of prescribing. A number of related factors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 22 publications
1
37
1
2
Order By: Relevance
“…and, as there was no way of inferring this from the data, the following contextual evidence was considered: first there is no contractual requirement for GPs to enter a diagnostic code before treating a patient for depression; by introducing a structured assessment for depression with penalties for non-completion, the General Medical Services contract at the time of the study may have disincentivised GPs from coding some patients. Second, GPs commonly report feeling pressured into prescribing an antidepressant with questionable indications, 6 and the researchers in the present study wished to capture these cases which may be less likely to receive a diagnostic code. In view of these contextual factors, it was decided to include in the primary analysis all patients prescribed a new course of an eligible antidepressant.…”
Section: Competing Interestsmentioning
confidence: 99%
“…and, as there was no way of inferring this from the data, the following contextual evidence was considered: first there is no contractual requirement for GPs to enter a diagnostic code before treating a patient for depression; by introducing a structured assessment for depression with penalties for non-completion, the General Medical Services contract at the time of the study may have disincentivised GPs from coding some patients. Second, GPs commonly report feeling pressured into prescribing an antidepressant with questionable indications, 6 and the researchers in the present study wished to capture these cases which may be less likely to receive a diagnostic code. In view of these contextual factors, it was decided to include in the primary analysis all patients prescribed a new course of an eligible antidepressant.…”
Section: Competing Interestsmentioning
confidence: 99%
“…Interestingly, GPs themselves question if they are right to prescribe antidepressants to people who have social problems. 31 Meltzer et al reported in the National Psychiatric Morbidity Survey, that the most common response to how people deal with mental health problems was to try to cope with problems oneself. 32 Thompson et al found that the most common reasons for not consulting were 'I thought it would go away by itself' (27.2%) and 'I thought nothing could help' (17.3%).…”
Section: Health Beliefsmentioning
confidence: 99%
“…6 Qualitative studies suggest that GPs' decisions to prescribe for depression are not taken lightly. 7,8 However, their opinions about their prescribing habits may not reflect actual behaviour.…”
Section: Introductionmentioning
confidence: 99%